INTEGRATED NETWORK PHARMACOLOGY, MICROARRAY ANALYSIS AND MOLECULAR DYNAMICS TO IDENTIFY A SUBSET OF POTENTIAL CAMEL MILK AND URINE BIOACTIVE COMPOUNDS IN TREATING AUTISM SPECTRUM DISORDER - Mahmoud Kandeel; Mohamed A. Morsy; Khalid M. Al Khodair; Sameer Alhojaily (Journal of Animal and Plant Sciences, 2024)
Camel milk and urine (CMU) are traditionally known for their medicinal properties, with camel milk has been reported to improve Autism Spectrum Disorder (ASD) symptoms. ASD is a complex neurodevelopmental disorder with no universally effective treatment. This study employs integrated network pharmacology, cheminformatics, microarray analysis and molecular modeling approaches to explore the potential therapeutic effects of a subset of camel CMU compounds for ASD. In our study, CMU compounds were analyzed collectively to explore their combined therapeutic potential in treating ASD, with the final impact assessed based on individual bioactive compounds. The study utilized a combination of active compounds collection and screening, potential target genes screening against autism, pathway and functional enrichment analysis, network construction, protein-protein interaction (PPI) network, docking and ADMET profiling. Twenty-two active compounds were identified in camel CMU, with 169 genes found to be common targets. Ten hub ASD-related genes, comprising ESRI, AKT1, CTNNB1, EGFR, CASP3, ERBB2, MMP9, PTGS2, JAK2, and GSK3β. Network analysis revealed a multi-target and multi-pathway interaction, suggesting a synergistic effect of CMU compounds on ASD. Molecular docking studies indicated strong binding affinities between selected compounds and key target proteins associated with ASD, such as AKT1 and GSK3β. ADMET profiling confirmed the pharmacokinetic viability of these compounds as therapeutic agents and molecular dynamics simulations confirmed the top compounds-GSK3β complexes stability. This study provides a foundation for understanding the therapeutic potential of CMU compounds against ASD, highlighting their multi-target and multi-pathway mechanisms. CMU compounds, particularly homogentisic acid, 4-hydroxyphenylacetic acid, 4-hydroxyphenylpyruvic acid, and phenylpyruvic acid, have the potential to modulate biological pathways implicated in ASD.
Keywords: Autism; Camel milk; Network Pharmacology; Enrichment Analysis; Molecular Modeling